Power Quality Improvement Using Active Power Filters in Industrial Systems - Anindya, Mikaela Shopie; Zaro, Fouad; Popescu, Mihaela (RESWARA: Jurnal Riset Ilmu Teknik, 2025)
Power quality issues have become a critical concern in modern industrial systems due to the increasing use of nonlinear loads, power electronic converters, and renewable energy integration. These factors significantly contribute to harmonic distortion, reactive power imbalance, voltage fluctuations, and reduced power factor, which can degrade system performance and shorten equipment lifespan. This study aims to analyze the effectiveness of active power filters in improving power quality in industrial environments. The research adopts a qualitative analytical approach by synthesizing recent empirical and simulation-based studies on shunt, series, and hybrid active power filter configurations. The findings indicate that active power filters provide superior harmonic mitigation, dynamic reactive power compensation, and voltage stabilization compared to conventional passive solutions. Shunt active power filters are particularly effective in reducing current harmonics, while series active power filters address voltage-related disturbances such as sags and swells. The study concludes that active power filters represent a robust and flexible solution for enhancing industrial power quality, supporting compliance with international standards and improving overall system reliability.